Self-Esteem and Problematic Smartphone Use Among Adolescents: A Moderated Mediation Model of Depression and Interpersonal Trust - Li, Chen; Liu, Dong; Dong, Yan (Frontiers in Psychology, 2019)
Research has found that self-esteem is negatively associated with problematic smartphone use. However, the internal mechanisms underlying that relationship need further investigation. The purpose of this study was to investigate the roles of depression and interpersonal trust in the relationship between self-esteem and problematic smartphone use among adolescents. A questionnaire comprised of the Rosenberg Self-esteem Scale, Inclusive General Trust Scale, Self-rating Depression Scale, and personal questions was administered to 637 students (female = 355) at two middle schools in Shanghai, China. Correlation analyses, mediation analysis, and moderated mediation analysis were performed. A moderated mediation model was established, which revealed: (1) a significant negative association between self-esteem and problematic smartphone use, (2) depression mediated the relationship between self-esteem and problematic smartphone use, and (3) the influence of depression on the relationship between self-esteem and problematic smartphone use was moderated by interpersonal trust. The results indicated that low self-esteem was a risk factor, and interpersonal trust was a moderating factor for problematic smartphone use among adolescents in the sample. Building adolescents’ self-esteem and increasing their interpersonal trust might decrease their problematic smartphone use.